Improving Performance Through Entrepreneurial Knowledge and Innovation of Moment Coffee Employees in Kendari City - Mahrani, Sri Wiyati; Suprianto, Ghalib; Harafah, La Ode Muhammad (International Journal of Management and Education in Human Development, 2025)
Entrepreneurship knowledge and innovation have become two key elements in determining business success, both for beginners and existing businesses. This study aims to analyze the influence of Entrepreneurial Knowledge and Innovation on Employee Performance by looking at how these two factors interact with each other and influence the performance of a business. The population in this study was 34 Moment Coffee employees in Kendari City and the entire population was used as respondents in this study. This study reveals that Entrepreneurial Knowledge improves managerial skills and decision-making abilities, while innovation plays an important role in creating products and services that are able to meet market needs and maintain competitiveness. Based on this research, it was found that Entrepreneurial Knowledge and innovation have a positive and significant influence on Employee Performance, both in terms of profitability, competitiveness, and business sustainability.